Output-Based Aid in Ethiopia : Dealing with the 'Last Mile' Paradox in Rural Electrification - Maurer, Luiz (World Bank, Washington, DC, 2012)
Providing electricity to poor households in rural areas in Ethiopia is critical to improving the health and living conditions of the population, reducing poverty, and stimulating growth. A project supported by the Global Partnership on Output-Based Aid (GPOBA) is accelerating the pace of connections in electrified areas and fostering energy efficiency. The scheme provides a performance-based subsidy to the state-owned utility in Ethiopia linked to the delivery of pre-agreed outputs, including the connection and provision of services on a sustainable basis. As part of the connection package, poor households receive two compact fluorescent lamps (CFLs). The project has potential for scaling up with a future International Development Association (IDA) loan to the utility.